Physico-chemical properties of meso-tetrakis(p-methoxyphenyl)porphyrin (TMPP) incorporated into pluronic™ P-123 and F-127 polymeric micelles - Vilsinski, Bruno H. (2014)
The physicochemical properties (solubilization, structural organization and stability) of meso-tetrakis(p-methoxyphenyl)porphyrin (TMPP), a promising photosensitizer for photodynamic therapy, solubilized in polymeric micelles of tri-block copolymers PluronicTM P-123 and F-127, were studied. The formulations obtained by the solid dispersion method led to monomerization of TMPP in these copolymers. Solubility studies showed that P-123 solubilizes double the photosensitizer than F-127. The selfaggregation phenomenon was affected by the [TMPP]/[poloxamer] ratio and medium temperature. The decrease in the temperature of these systems promoted the formation of different kinds of TMPP aggregates intrinsically connected with the structural changes occurring in the micelles.